Explosive Nucleosynthesis Study Using Laser Driven γ-ray Pulses - Takehito Hayakawa (Quantum Beam Science, 2017)
We propose nuclear experiments using γ-ray pulses provided from high field plasma generated by high peak power laser. These γ-ray pulses have the excellent features of extremely short pulse, high intensity, and continuous energy distribution. These features are suitable for the study of explosive nucleosyntheses in novae and supernovae, such as the γ process and ν process. We discuss how to generate suitable γ-ray pulses and the nuclear astrophysics involved.